HOW DOES THE CAMPUS PARTY CULTURE INFLUENCE STUDENT ACADEMIC PERFORMANCE AND WELBEING? - Ergashova Umida; Fozilbek Orzibekov (TADQIQOTLAR, 2025)
Abstract This paper explores the impact of campus party culture on students’ academic performance and overall wellbeing. As social gatherings and nightlife activities become increasingly embedded in university life, there is growing concern about their influence on students’ mental health, academic success, and lifestyle choices. Drawing on existing literature and historical perspectives, this study examines how party culture affects student behavior, motivation, and time management, highlighting both the potential benefits and drawbacks. While party culture may foster social bonding and stress relief, it can also lead to academic decline, poor health outcomes, and risky behaviors if not managed properly. This paper aims to provide a balanced view to understand the relationship between partying and the academic and personal lives of university students.